The sum of those is 800,201
Answer:
A) -1
Step-by-step explanation:
![\frac{3 + 2\sqrt{5} }{2\sqrt{5}-3 } \\](https://tex.z-dn.net/?f=%5Cfrac%7B3%20%2B%202%5Csqrt%7B5%7D%20%7D%7B2%5Csqrt%7B5%7D-3%20%7D%20%5C%5C)
We can rewrite 2√5 - 3 as -(3 + 2√5)
Therefore,
![\frac{3+ 2\sqrt{5} }{-(3 + 2\sqrt{5} )} \\](https://tex.z-dn.net/?f=%5Cfrac%7B3%2B%202%5Csqrt%7B5%7D%20%7D%7B-%283%20%2B%202%5Csqrt%7B5%7D%20%29%7D%20%5C%5C)
We can cancel out 3 + 2√5 both in the numerator and the denominator. So we get
= 1/-1
= -1
Answer : A) -1
Thank you.
We have that
<span>log10 E = 4.4 + 1.5<span>M
</span></span>E=<span>the released energy in Joules (J)
M= </span><span>earthquake measures---------- > 3.6
</span>log10 E = 4.4 + 1.5*3.6
log10 E = 9.8----------> E=10^(9.8)= 6.309573444 x10^9 J
<span>
the answer is </span>6.309573444 x10^9 J<span>
</span>
Answer:
false
Step-by-step explanation:
X is equal to Y
therefore,
X = Y
X= false
Y = false
so,
false = false
Answer:
this is how you do it.. press the crown button in an answer
Step-by-step explanation: